Competition Law in India - Ramappa, T. (Oxford University Press, 2006)
India, till 2002, did not have a law dealing specifically with antitrust issues. It was in this context that a separate law dealing with competition and antitrust issues was considered necessary and the Competition Act, 2002, was passed. Enacted to fulfil India’s obligations under the WTO agreements, the Act replaced the then existing Monopolies and Restrictive Trade Practices Act, 1969 (the MRTP Act), which was considered inadequate and archaic for the purpose of meeting the objectives of competition policy. This substantially revised edition discusses the Competition Act, 2002, and subsequent amendments to it, in 2007 and 2009. Following the 2007 amendment, the Competition Commission became a market regulator and the Competition Appellate Tribunal was established. The 2009 amendment provided for a mechanism to dispose of the cases pending before the MRTP Commission. The book makes a detailed study of key issues including anti-competitive agreements, abuse of dominant position, and combinations (acquisitions and mergers). It further analyses the roles of authorities such as the Competition Commission of India, the Director-General, and the Competition Appellate Tribunal in enforcing the provisions of the Act. The book also undertakes a comparative study of competition law in the US, UK, and EU with emphasis on important judgements.